The motivating factors that lead the participation among the Bumiputera women in Small and Medium Enterprise (SME): a case study in Melaka Tengah District, Malaysia / Mohamed Fajil Abdul Batau … [et al.] - Abdul Batau, Mohamed Fajil; Ayob, Nor Azira; Yais Razali, Hazariah; Aminnuddin, Adnan; Abdul Rahman, Farah Adilla (Faculty of Administrative Science and Policy Studies, 2012)
Bumiputera Women Entrepreneurs in Malaysia appear to have put the place in the business arena particularly in the Small and Medium Enterprise (SME). Thus, this study aims to investigate the involvement factors of Bumiputera women in the business of Small and Medium Enterprise (SME) in the Melaka Tengah district. Questionnaires instrument were used as a method of data collection and distributed to 80 Malay Bumiputera women entrepreneurs which involved in entrepreneurial activities in Malacca. Data analysis through correlation analysis, analysis of variance and regression analysis is used to achieve the objectives of the study by using SPSS 19. This study identified significant relationship between the factors involvement women entrepreneurs in SMEs. Results showed that the main factor that drove many Malacca Malay Women entrepreneurship was Financial Factors. In addition factors such as Types of Family Background and Academic Qualification are also factors that encouraged them to become entrepreneurs. Besides that, this finding can contribute to the additional information, data and research focus in issues relating to Malay women's participation in the Small and Medium Enterprise (SME) in Malacca and also expected to provide new ideas for the improvement on the program, financial assistance and the state government and agencies involvement in assisting the problems that arise among Bumiputera women entrepreneurs. In addition, hopefully it gives new information for the future research.